Selective high impedance surface active region loading of archimedean spiral antenna - Mohamad, Sarah Yasmin; Cahill, Robert; Fusco, Vincent (IEEE, 2014)
We show that a significant increase in the gain and front-to-back ratio is obtained when different high impedance surface (HIS) sections are placed below the active regions of an Archimedean spiral antenna. The principle of operation is demonstrated at 3, 6, and 9 GHz for an antenna design that employs a ground plane composed of two dissimilar HISs. The unit cells of the HISs are collocated and resonant at the same frequency as the 3- and 6-GHz active regions of the wideband spiral. It is shown that the former HIS must also be designed to resonate at 9 GHz to avoid the generation of a boresight null that occurs because the structure is physically large enough to support higher-order modes. The improvement that is obtained at each of the three frequencies investigated is shown by comparing the predicted and measured radiation patterns for the free space and HIS-backed antenna.